SARAWAKUS LLOYD, A GENUS OF THE PYRENOMYCETE FAMILY HYPOCREACEAE - MIEN A. RIFAI (REINWARDTIA, 1969)
The scope of the monotypic genus Sara.wa.kus is enlarged to enable it to accommodate the newly described species Sarawakus sucoisus Rifai. A complete taxonomic revision of the genus is presented, in which it is shown that Sarawakus belongs to the Hypocreaceae and not to the Xylariaceae as some authors have suggested. Hypocrea gelaiinosa (Tode ex Fr.) Fr. subsp. oligotheea Penz. & Sacc. is accorded specific status as Hypocrea oligotheea (Penz. & Sacc.) Rifai and Phaeocreopsis pezizaeformis Boedijn is transferred to Hypocreopsis.